A simulation study of photovoltaic system integrated with phase change material using ANSYS - Salimen, Nurfarhana (2021)
Temperature regulation in photovoltaic (PV) systems is crucial for enhancing PV performance. Passive cooling with a phase transition material (PCM) is one approach for dealing with overheating. Crude Palm Oil (CPO), which is more sustainable, and abundant is preferred in Malaysia. The potential of CPO as a PCM is being studied further by a simulation study utilizing CFD software, ANSYS to model the temperature differences and distribution of the PV-PCM system. A comparison of the temperature difference for the front PV-PCM system with and without PCM, temperature distribution, and contour of the system was also done. The main findings show that the average temperature difference for PV systems with and without CPO is around 50.7%, indicating that the PV system without PCM heats up approximately twice as much as the system with PCM. For temperature distribution,the front surface of the system maintains the temperature at 326.6K for about 992.4s over the melting point of the PCM (T=308.8K), whereas the back appears to have a linearly increasing temperature with time. From comparison analysis, the CPO is the most practical approach for lowering the temperature of the PV-PCM system that works in the ambient temperature of 27oC, suited Malaysian weather. CPO has tremendous potential for regulating system temperature. Additional experimental work can be performed to validate the simulation.